1985
DOI: 10.1111/j.1469-8749.1985.tb03763.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolongatión of Walking in Duchenne Muscular Dystrophy With Lightweight Orthoses; Review of 57 Cases

Abstract: SUMMARY Fifty‐seven boys with Duchenne muscular dystrophy aged between 6 years 3 months and 13 years 6 months, who were at the point of losing the ability to walk or had recently done so, were fitted with lightweight knee‐ankle‐foot orthoses to re‐establish walking. 47 walked well and independently in their orthoses, achieving good stability and confidence. 20 are still ambulant; the other 27 stopped walking at intervals ranging from eight to 48 months. Prolongatión of walking prevented the development of scol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(14 citation statements)
references
References 10 publications
(7 reference statements)
0
11
0
3
Order By: Relevance
“…26 Gordon et al 27 concluded that percutaneous lengthening of the medial hamstrings was a useful option in ambulant children with CP undergoing a variety of concomitant operations. They reported significantly Table III.…”
Section: Discussionmentioning
confidence: 99%
“…26 Gordon et al 27 concluded that percutaneous lengthening of the medial hamstrings was a useful option in ambulant children with CP undergoing a variety of concomitant operations. They reported significantly Table III.…”
Section: Discussionmentioning
confidence: 99%
“…There are some experts who feel the use of KAFO’s prolongs ambulation in DMD by one to three years. 45, 46 Although the literature to support this is poor, 47 the greater reason why fewer patients are using KAFO bracng in recent years is due to the efficacy of corticosteroids in prolonging ambulation. In addition, the compliance of DMD patients with KAFO bracing is variable.…”
Section: Management Of Contracturesmentioning
confidence: 99%
“…Rehabilitation in knee-ankle-foot orthoses (KAFOs) is offered to boys with DMD at the end of independent ambulation, and is effective in prolonging walking for an average of 18 months to 2 years 12. The technique entails custom-built KAFOs, and in the past used to require surgical release of the Achilles tendon to reduce ankle contracture and allow fitting of the KAFO, and is generally well tolerated 13.…”
Section: Physiotherapy and Orthosesmentioning
confidence: 99%